PENGALAMAN BELAJAR SISWA SEKOLAH DASAR DALAM PENGGUNAAN SMARTBOARD: SYSTEMATIC LITERATURE REVIEW - Sabila Fijra Hidayatika; Najla Putri, Shofyah; Adrias (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the influence of smartboard use on elementary school students' learning experience across cognitive, social-affective, and ease-of-learning dimensions. A qualitative approach with Systematic Literature Review (SLR) method using the PRISMA protocol was employed. Articles were retrieved from Google Scholar, Portal Garuda, and SINTA databases, published between 2020 and 2026. From 25 articles identified, 10 met the inclusion criteria and were analyzed using narrative synthesis. The findings reveal three major themes: (1) smartboard consistently enhances students' cognitive experience across multiple subjects including mathematics, PPKn, IPS, and reading comprehension; (2) smartboard strengthens social and affective engagement by increasing motivation, classroom interaction, and emotional involvement; and (3) smartboard effectively reduces cognitive load, making learning more accessible for elementary-age learners. These three dimensions are interrelated and mutually reinforcing, indicating that smartboard use produces a holistic learning experience beyond academic achievement alone. This study concludes that smartboard integration in elementary education supports a more meaningful and multidimensional learning experience for students.